MINERALOGICAL IDENTIFICATION AND CHARACTERISATION OF SASYAKA-AN AYURVEDIC DRUG - Pandey, Prem Shankar (International Journal of Ayurveda and Pharma Research, 2020)
The present study deals with the identification and mineralogical characterization of Sasyaka having various medicinal properties used in Ayurvedic system of medicine. Sasyaka synonyms Tuttha is one among Maharasa and that occurs in nature is called Sasyaka and that which is made artificially is called Tuttha, anyone can be used in place of the other. Chemically Sasyaka is copper iron sulphide and Tuttha is hydrated copper sulphate. Sasyaka reflects the color similar to the neck of peacock and is heavy in weight whereas Tuttha is blue stone or blue vitrol. Sasyaka is used therapeutically in the form of Bhasma for the treatment of diseases of eyes, skin diseases, ulcer, sinus, worm infection, vitiligo, obesity, diabetes, pain, asthma, hyperacidity, hemorrhoids, leprosy, chronic diarrhea, dysentery, leucorrhea and gonorrhea. However, raw drug identification and standardization play a vital role for assuring the therapeutic potential of the final drug. The sample of Sasyaka was collected from local market and authenticated by the subject expert and further analyzed by classical and modern methods. The results showed that the Sasyaka possess metallic luster, neck of peacock color, orthorhombic crystal structure, high specific gravity, irregular fracture and positive magnetism. All the physical properties of mineral Bornite together with Electron Probe Micro Analysis (EPMA) study are very well match with acceptable characteristics of Sasyaka as described in Ayurvedic classic. Sasyaka is thus identified as mineral Bornite (Cu5FeS4).